CLIMACTERIC: STAGE AT WOMEN - Alexandra Santos Schettert do Valle, Patrícia (2016)
We understand that sexuality is an inherent part of the human being at any stage of the life cycle it is present without having affected their intensity. After all, it is not reduced to the sexual act, but goes far beyond the purely physical perceptions. The lack of spaces where climacteric women can discuss their sexuality, learn a little more about the intense changes in your body and your back was that the Tutorial Education Program: Sexuality, sexual education located in IFRJ campus Realengo (RJ), establishing a project for the community of Catholic women in climacteric and menopausal phase aiming to create a space and lead a discussion of the biopsychosocial changes inherent to this stage and achievements of development or resumption of their sexuality in a pleasurable way.